Targeted Gene Knockouts by Protoplast Transformation in the Moss Physcomitrella patens - Zhu, Lei (Frontiers in Genome Editing, 2021)
Targeted gene knockout is particularly useful for analyzing gene functions in plant growth, signaling, and development. By transforming knockout cassettes consisting of homologous sequences of the target gene into protoplasts, the classical gene targeting method aims to obtain targeted gene replacement, allowing for the characterization of gene functions in vivo. The moss Physcomitrella patens is a known model organism for a high frequency of homologous recombination and thus harbors a remarkable rate of gene targeting. Other moss features, including easy to culture, dominant haploidy phase, and sequenced genome, make gene targeting prevalent in Physcomitrella patens. However, even gene targeting was powerful to generate knockouts, researchers using this method still experienced technical challenges. For example, obtaining a good number of targeted knockouts after protoplast transformation and regeneration disturbed the users. Off-target mutations such as illegitimate insertions mediated by nonhomologous end joining and targeted insertion wherein one junction on target but the other end off-target are commonly present in the knockouts. Protoplast fusion during transformation and regeneration was also a problem. This review will discuss the advantages and technical challenges of gene targeting. Recently, CRISPR-Cas9 is a revolutionary technology and becoming a hot topic in plant gene editing. In the second part of this review, CRISPR-Cas9 technology will be focused on and compared to gene targeting regarding the practical use in Physcomitrella patens. This review presents an updated perspective of the gene targeting and CRISPR-Cas9 techniques to plant biologists who may consider studying gene functions in the model organism Physcomitrella patens.